Susceptibility Testing for the Polymyxins: Two Steps Back, Three Steps Forward? - Vasoo, Shawn (2018)
Optimizing and standardizing susceptibility testing for the polymyxins have become pressing issues, given the rise in multidrug-resistant Gram-negative bacilli. Recently, both the CLSI and EUCAST have recommended broth microdilution (BMD) (without polysorbate) as the reference method for polymyxin susceptibility testing. In this issue, K. L. Chew et al. (J Clin Microbiol 55:2609–2616, 2017, https://doi-org.ezlibproxy1.ntu.edu.sg/10.1128/JCM.00268-17) compare the performances of three commercial BMD panels and the Etest to the reference, BMD, for polymyxin B and colistin, using 76 Enterobacteriaceae isolates (21 of which were mcr-1 positive). Although none of the commercial BMD panels strictly met FDA performance standards in this evaluation, possibly because of the small number isolates tested, the Sensititre panel achieved >90% categorical agreement for both polymyxin compounds. These results also reaffirm CLSI and EUCAST guidance that gradient diffusion testing, which had unacceptable error rates, should be abandoned. In a simulated analysis with lowered breakpoints (susceptible, ≤1 mg/liter; intermediate, 2 mg/liter; resistant, ≥4 mg/liter), error rates and agreement were improved across the various methods and the rate of detection of mcr-1-positive isolates improved. These observations, taken together with recent pharmacokinetic data on optimizing target attainment for the polymyxins, suggest that more-stringent (lower) breakpoints may be reasonable, although such an approach may be limited by the inherent reliability of current testing methodologies and a lack of robust clinical correlative data, which are sorely needed.